Preoperative Naples prognostic score is a reliable prognostic indicator for newly diagnosed glioblastoma patients - Li, Junhong; Yang, Wanchun; Yuan, Yunbo; Zuo, Mingrong; Li, Tengfei; Wang, Zhihao; Liu, Yanhui (Frontiers in Oncology, 2022)
Background: Glioblastoma (GBM) accounts for approximately 80% of malignant gliomas and is characterized by considerable cellularity and mitotic activity, vascular proliferation, and necrosis. Naples prognostic score (NPS), based on inflammatory markers and nutritional status, has prognostic ability in various cancers. In the current study, we aim to explore the prognostic value of operative NPS in GBM patients and compare the prognostic ability between NPS and controlling nutritional status (CONUT). Materials and methods: The retrospective analysis was carried out on consecutive newly-diagnosed GBM patients who had underwent tumor resection at West China Hospital from February 2016 to March 2019. All statistical analyses were conducted using SPSS software and R software. Results: A total of 276 newly-diagnosed GBM patients were enrolled in the current study. Overall survival (OS) (p<0.001) and tumor location (p=0.007) were significantly related NPS. Serum albumin concentrate, cholesterol concentrate, neutrophil to lymphocyte ratio, lymphocyte ratio, and CONUT score were all significantly associated with NPS (p<0.001). Kaplan-Mier curve indicated NPS (log-rank test, p<0.001) and CONUT score (log-rank test, p=0.023) were significantly associated with OS. Multivariate Cox regression revealed that NPS and CONUT score both served as independent prognostic indicators. Prognostic model with NPS had strongest prognostic capability and best model-fitting. Conclusion: In the current study, NPS is found an independent prognostic indicator for patients with newly-diagnosed GBM, and the prognostic ability of NPS is superior to CONUT score.